(untitled) (Revista Educação, Artes e Inclusão, 2025)
The insertion and application of art in mental health care contexts is the central object of this article. To achieve this proposal, the pioneering experiences of dialogue between these two fields in psychiatric ateliers in the 20th century are revisited and problematized. Based on these references and highlighting the work coordinated by Osório César and Nise da Silveira, we inventoried and articulated proposals, experiences and directions related to the inclusion of art within the scope of Therapeutic Workshops, a space for the insertion of artists and art educators in public care policies to mental health.